Evaluation of maize, soybean flour blends for sour maize bread production in Nigeria - Edema, M.; Sanni, Lateef O.; Sanni, A. (2005)
Examination of the functional properties of three different flours/meals and two blends of maize meal and soybean-flour (ratios 9:1 and 8:2, maize:soybean) were carried out. Properties examined included amylose content, bulk density, dispersibility, swelling power, water absorption capacity and viscoelastic properties. The effect of the different flour/meal samples on the properties of sour maize bread were evaluated by baking bread samples with the different flours/meals using a mixed starter culture of Lactobacillus plantarum and Saccharomyces cerevisiae. All flour/meal samples differed, sometimes significantly (p 0.05) in their functional properties. Significant positive correlations existed among the functional properties of the flours at the 1% level (2-tailed). The maize meal/soy flour blends MSA (maize meal and soybean flour mixed in ratio 9:1) and MSB (maize meal and soybean flour mixed in ratio 8:2) did not differ significantly from each other in functional properties except for amylose content. MSA was adjudged the best flour blend for sour maize bread production as its bread had the highest score for overall acceptability (6.1) and other sensory parameters evaluated.